As usual : Fred and Stan Coulton in the Great War, 1916-1918 - Coulton, Fred; Gardoll, Lisa ([Goondiwindi, Queensland] : Lisa Gardoll, 2021)
Annotation. Fred and Stan Coulton enlisted and served with the 2nd Pioneer Battalion, Australian Imperial Force, in Egypt and on the Western Front. Fred kept a daily diary throughout the war years, 1916 - 1918, and regularly wrote to friends and family at home, sending souvenirs or portrait postcards when possible. Throughout the extended family, numerous items related to Fred and Stan in the Great War have been carefully preserved for more than 103 years. The family collection has been collated into one book providing a central resource for present and future Coulton descendants. Supplementary material has been incorporated to add further context to the story of Fred and Stan, detailing where the brothers were located, what tasks the battalion was employed to do, and providing an outline of the relevant battle timeline. The book was produced for the 2022 Coulton Family Reunion.
Includes bibliographical references and index.
Keywords: World War, 1914-1918 -- Personal narratives, Australian; World War, 1914-1918 -- Australia -- Biography; Soldiers -- Australia -- Correspondence; Australian